Hubungan Beban Kerja Dengan Burnout Syndrome Pada Perawat Di Ruang Rawat Inap Rumah Sakit Bhayangkara Tingkat III Manado - Kaani, Jimri Novrian; Mariana Larira, Dina; Juwita Mauren Toar (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background. A nurse is someone who has the authority to provide nursing services that are humanistic in nature so that it can cause a separate workload for the nurse and cause stress to the nurse if the stress has a long-term impact it will cause physical, psycholigical fatigue or known as burnout syndrome. Aim. To determine the relationship between workload and burnout syndrome in nurses at Bhayangkara Hospital Level III Manado. Methods. This study used a cross sectional approach with 49 respondents and used the spearmen rank statistical test. Results. In this study obtained 42 heavy workload (85.7%) and 48 moderate burnout (98%) Statistical test results obtained P value = 0.000 then p value < α value (0.05). Discussion. Heavy workload can be one of the triggers for individuals affected by burnout syndrome. Conclusion. there is a relationship between workload and burnout syndrome in nurses in the inpatient room of Bhayangkara Hospital Level III Manado.